2022
DOI: 10.21203/rs.3.rs-2019827/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of the Accuracy of the Ishii Test in Diagnosing Severe Sarcopenia among Multi- ethnic Middle-aged to Older Adults: Results From the West China Health and Aging Trend Study

Abstract: OBJECTIVES: This study was designed to establish the diagnostic utility of the Ishii test, which gauges the odds of severe sarcopenia based on the results of an equation based upon age, grip strength, and calf circumference among middle-aged and older adults in Western China. METHODS: This study incorporated adults ≥ 50 years of age from the West China Health and Aging Trend (WCHAT) study. Severe sarcopenia was defined as per the AWGS2019 recommendations, with the odds of severe sarcopenia being estimated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…One possible reason for the difference is that the number of sarcopenia cases was smaller in women than in men in our study (women, 55; men, 129); therefore, our receiver operating characteristic curve analysis of the Ishii score for women was less reliable than that for men. This hypothesis is supported by several studies that demonstrated no sex differences in the predictability of the Ishii score for the presence of sarcopenia in patients with non–heart failure 12,25 . The lower prevalence of sarcopenia in women may be attributed to the differences in age‐associated muscle loss.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…One possible reason for the difference is that the number of sarcopenia cases was smaller in women than in men in our study (women, 55; men, 129); therefore, our receiver operating characteristic curve analysis of the Ishii score for women was less reliable than that for men. This hypothesis is supported by several studies that demonstrated no sex differences in the predictability of the Ishii score for the presence of sarcopenia in patients with non–heart failure 12,25 . The lower prevalence of sarcopenia in women may be attributed to the differences in age‐associated muscle loss.…”
Section: Discussionmentioning
confidence: 58%
“…This hypothesis is supported by several studies that demonstrated no sex differences in the predictability of the Ishii score for the presence of sarcopenia in patients with non-heart failure. 12,25 The lower prevalence of sarcopenia in women may be attributed to the differences in age-associated muscle loss. Men typically experience a gradual loss of muscle mass as they age, while the decline in muscle mass among women is generally minimal or only slightly substantial.…”
Section: Discussionmentioning
confidence: 99%